Intracervical Artificial Insemination using Frozen Semen of Boer buck on Pote Does at Different Times of Estrus - Susilowati, Suherni; Tri Wahyu Suprayogi; Tatik Hernawati; Yossy Imam Candika; Widya Paramita Lokapirnasari (Universitas Airlangga, 2023)
Pote goats are kept by the rural community in Bangkalan Regency, Madura Island, Indonesia. Estrus symptoms in goats are usually unclear, causing low fertility. This study aimed to determine the intracervical artificial insemination at early and mid-estrus on the Pote does. The 24 the does were randomly divided into two groups and estrous synchronization with PGF2α of 200 µg intramuscularly, twice injections with 11 days intervals. The T1 groups of estrus the Pote does were inseminated at early estrus (0-12 hours). Meanwhile, T2 groups of estrus the Pote does were inseminated at mid-estrus (12-24 hours after signs of estrus appeared. The insemination conducted artificially using post-thawed Boer semen. The observed variables were non-return rate at day 21 post-insemination (NRR21), and pregnancy rate (PR) based on abdominal palpation diagnosis. The result showed that post-thawed Boer buck was qualified (sperm motility more than 40%) for artificial insemination. All of the Pote does were estrus after twice PGF2α intramuscular injection with 11 days intervals. The onset of estrus was 48-72 hours after the second injection PGF2α. The NRR21 and PR ranged from 66.66-100% and 37.50-66.66%, respectively. The NRR21 and PR of the T2 group were higher than those of the T1 group. It could be concluded that intracervical artificial insemination on Pote the does at mid-estrus were more effective, resulting in higher NRR21 and PR than those at early estrus.